Analisis Etika Profesi dan Pertanggungjawaban Pidana Influencer dalam Fenomena Penyebaran Judi Online di Media Sosial - Mahdiah Amelia; Tessy Wicaksono; Azka Silviya Nita; Hedrolis bago; Ushie Rahmadian; Yunita Yunita (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of information and communication technology has brought about major changes in the way society interacts and conducts activities. Social media has now become a limitless public space that makes it easy for anyone to share information, express opinions, and even carry out various economic activities. This study aims to analyze the forms and limits of criminal liability for influencers who promote online gambling by referring to the provisions in the Criminal Code (KUHP) and the Electronic Information and Transactions Law (UU ITE). Furthermore, it examines the application of digital professional ethics principles and deontology principles in promotional activities carried out by influencers, in order to assess the extent to which these actions violate moral and professional obligations as public figures in the digital space. This study uses a normative legal method (normative juridical) with a qualitative-descriptive approach. This approach is used to examine and understand the positive legal norms stipulated in laws and regulations, as well as legal principles related to professional ethics and criminal liability. This study finds that the phenomenon of online gambling promotion by influencers on social media has negative social, economic, and moral impacts, especially for the younger generation. Based on a normative legal analysis, influencers who promote online gambling may be subject to criminal liability under the Electronic Information and Transactions Law (ITE) and the Criminal Code, particularly if proven to meet the elements of participation and intent.